The Question of Culture - Krakauskas, Edmundas (Problemos, 1996)
This is the question of man – not only a question of a notion. As a theoretical issue, it was formulated by Romantic thinkers in the 18th century. The industrial society has been a stimulus for the rethinking of the originality of man. The author supposes that, for further discussion of the question, a clarification of the evaluative approach is more fruitful than the repudiation of this approach.